Comparison of The Effectiveness of Intermittent and Continuous Pantoprazole Therapy in Peptic Ulcer Disease Bleeding - Ade Wirastuti; Sri Rahmat Molidia; Salsabela Salsabela; Kharina Anisya; Fortunata Saesarria Deisberanda; Kathina Deswi Aqsa; Muhammad Nur Ajwad; Abdurraafi' Maududi Dermawan; Fakhruddin Fakhruddin; Rommy Rommy (Rumah Sakit Akademik Universitas Gadjah Mada, 2026)
Background: Peptic ulcer disease with melena is commonly encountered in clinical practice. Pantoprazole is widely used to control bleeding and heal ulcers, but there is still debate regarding the effectiveness of intermittent bolus administration compared to continuous infusion.Objective: To review and evaluate the literature on the comparative effectiveness of pantoprazole administered via intermittent bolus versus continuous infusion.Methods: This study employed a narrative literature review design. Literature searches were conducted in the PubMed, Google Scholar, ProQuest, and Sage Journals databases for publications from 2020 to 2025 using the keywords: “pantoprazole,” “continuous infusion,” “intermittent bolus,” “effectiveness,” “bleeding,” and “peptic ulcer disease”.Result: Four articles met the inclusion criteria. Two studies reported no significant difference between intermittent bolus and continuous infusion administration. One study found that intermittent bolus administration was associated with a shorter length of stay, whereas another recommended continuous infusion for patients at high risk of upper gastrointestinal bleeding. There was heterogeneity in study design and reported outcomes.Conclusion: There is no significant difference between continuous infusion and intermittent bolus administration of pantoprazole; given the limited number and quality of studies, further research is needed.